1999
DOI: 10.1007/s100530050402
|View full text |Cite
|
Sign up to set email alerts
|

Conductance quantization in multiwalled carbon nanotubes

Abstract: Abstract. We present results of carbon nanotube conductance measurements. The experiments were performed using an scanning probe microscope (SPM) system where a carbon nanotube fiber is connected to the SPM tip and then lowered into a liquid mercury contact. Experiments were also performed using a modified transmission electron microscope (TEM) specimen holder supplied with piezo and micrometer positioning system. Thus the contacting process of the nanotubes with the mercury could be monitored while simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 15 publications
5
56
0
Order By: Relevance
“…The conductance gets reduced by a factor close to two, very much like in the ferromagnetic computations. More importantly however, this behavior is in qualitative agreement with experimental results 11,23 if we associate the lower and upper bunch of curves in Fig. 5 with the major plateaux of the conductance of MWCNT immersed into Hg.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The conductance gets reduced by a factor close to two, very much like in the ferromagnetic computations. More importantly however, this behavior is in qualitative agreement with experimental results 11,23 if we associate the lower and upper bunch of curves in Fig. 5 with the major plateaux of the conductance of MWCNT immersed into Hg.…”
Section: Resultssupporting
confidence: 89%
“…The conductance suppression in MWCNTs below the expected value for the infinite homogeneous tube has been experimentally well documented. 11,23 In our model system charge-transfer induced changes in the band structure of the DWCNT lead to a reduction (roughly to 4e 2 /h) of the conductance -as one can see in the upper curves in Fig. 5.…”
Section: Resultsmentioning
confidence: 65%
“…Metallic carbon nanotubes are near ideal conductors of current [1,2,3,4,5]. While a single nanotube can be used as an interconnect in molecular electronics, nanotube arrays have shown promise as more conventional interconnects in conjunction with silicon technology [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The non crossing subbands of small diameter nanotubes do not carry current due to their large band gap. In contrast, large diameter nanotubes experimentally show an increase in conductance with applied bias [1,2,12,13]. Reference [14] suggested that as the diameter increases, electrons may tunnel into non crossing subbands, thus causing an increase in differential conductance with applied bias.…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that the single-walled carbon nanotubes (SWCNTs) or their bundles show the classical transport properties such as Coulomb blockade, energy quantization, Luttinger liquid characteristics and ballistic transport [4,5]. It is usually difficult for the multi-walled carbon nanotubes (MWCNTs) to make electrical contact between neighbor graphite layers because the total conductance is significantly limited by the charge carrier transport [6]. Variable range hopping (VRH) conduction, weak localization, resonant tunneling phenomena, universal conductance fluctuations, or Aharanov-Bohm oscillations of magnetoresistance, may appear or become dominant in the electrical transport of MWCNTscontaining systems [7,8].…”
Section: Introductionmentioning
confidence: 99%